Rheology assessment of cellulose acetate spinning solution and its influence on reverse osmosis hollow fiber membrane performance - Idris, Ani; Ismail, A. F.; Gordeyev, S. A.; Shiltom, S. J. (2003)
Cellulose acetate spinning solution used to produce reverse osmosis (RO) hollow fiber membranes was rheologically assessed using a rotational rheometer and an optical shear cell. Rheology measurements which involved flow curves were carried out so as to obtain the values of power law coefficients, n and k. The power law behaviour, normal force and flow profiles generated provided clues regarding phase inversion and molecular orientation. These rheological results are then correlated to the performance of cellulose acetate RO hollow fibers spun at different extrusion shear rates. The results suggest that extrusion shear is linked indirectly to phase inversion through induced molecular orientation, which in turn, affects the subsequent dry/wet precipitation stages in spinning. As the extrusion shear rate increases, the level of shear experienced at the walls of the spinneret also increases, thus leading to greater molecular orientation, resulting in membranes with higher rejection and flux rates.